Three new Sinopoda species (Araneae: Sparassidae) from southern China - Zhang, Bao-Shi; Zhang, Zhi-Sheng; Zhang, Feng (Zootaxa, 2015)
Three new species of the huntsman spider genus Sinopoda Jäger, 1999, collected from Sichuan Province and Chongqing Municipality, P. R. China, are described: Sinopoda cochlearia sp. nov. (male, female), S. globosa sp. nov. (male, female) and S. longiducta sp. nov. (male, female). All three new species were collected from native forest by hand.